Implementasi vpn berbasis ipsec menggunakan fortigate pada rumah sakit atma jaya - Arifin, Nurul; Putra, Jordy Lasmana (FORMAT, 2024)
As a hospital that implements the SIMRS system and technology (Hospital Management Information System) that supports hospital management so as to create optimal service. For this reason, all support will certainly require a secure information and communication technology and has become a major requirement, including in terms of processing information and exchanging information. Atma Jaya Hospital already has computer network technology that supports employees' needs for data access through computer networks. However, the computer network technology currently owned cannot be utilized optimally by the hospital, so that the safety of accessing data from outside the hospital is not guaranteed by both doctors and employees. The current condition is that access to data from outside the hospital uses third-party applications, whose history cannot be known and is not deactivated. By maximizing the existing Fortigate in the hospital network infrastructure, we implemented a VPN with the IPSec method to access hospital data for doctors and employees, so that it can be more calm and guaranteed security from both the hospital and doctor or employee sides.